Trade Liberalization and Real Exchange Rate Movement - Li, Xiangming (IMF Working Papers; Working Paper ;, 2003)
Although theory suggests that the real exchange rate should depreciate after a credible trade liberalization but could appreciate temporarily with a noncredible one, little empirical evidence exists. Unlike existing studies that use either indirect tests or unreliable openness measures, this paper uses an event study based on carefully documented trade liberalization in 45 countries. The result shows that real exchange rates depreciate after countries open their economies to trade. In countries with multiple liberalization episodes, however, real exchange rates appreciate during early episodes, suggesting that partial or noncredible trade liberalizations are associated with real appreciation.